2022
DOI: 10.1158/1078-0432.ccr-21-1943
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K/AKT Pathway Is a Potential Mechanism of Treatment Resistance in Small Cell Lung Cancer

Abstract: Purpose: Here, we have investigated treatment resistance mechanisms in small cell lung cancer (SCLC) by focusing on comparing the genotype and phenotype in tumor samples of treatment-resistant and treatment-sensitive SCLC. Experimental Design: We conducted whole-exome sequencing on paired tumor samples at diagnosis and relapse from 11 patients with limited-stage (LS)-SCLC and targeted sequencing of 1,021 cancer-related genes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…3F). Notably, signaling pathways known to drive tumorigenesis in SCLC and currently investigated in targeted therapy trials (DLL3-targeting molecules for the NOTCH pathway or PI3KCA/AKT inhibitors for the MAPK pathway) were specifically implicated in relapsed CD56+CTC 19, 20 . These results suggest that overcoming relapse after first-line systemic treatment may require targeting these signaling pathways, as we speculate this gives a selective advantage for resurgent SCLC clones.…”
Section: Resultsmentioning
confidence: 99%
“…3F). Notably, signaling pathways known to drive tumorigenesis in SCLC and currently investigated in targeted therapy trials (DLL3-targeting molecules for the NOTCH pathway or PI3KCA/AKT inhibitors for the MAPK pathway) were specifically implicated in relapsed CD56+CTC 19, 20 . These results suggest that overcoming relapse after first-line systemic treatment may require targeting these signaling pathways, as we speculate this gives a selective advantage for resurgent SCLC clones.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the repurposing of existing drugs, such as tyrosine kinase inhibitors, Hedgehog signaling inhibitors, anti-apoptotic inhibitors, and anti-angiogenesis agents, has not had a meaningful clinical impact in treating SCLCs [ 13 , 39 , 40 ]. Gene mutations (e.g., PIK3CA , PTEN , and RICTOR ) and activation of the PI3K/AKT/mTOR have been reported in genomic and proteomic profiling studies of SCLC tumor samples; however, there have been notable discrepancies in the results, due perhaps to relatively small sample sizes, differences in population (e.g., race, naïve or chemo-resistant) and sequencing techniques [ 8 , 10 , 12 , 41 ]. Nevertheless, the effectiveness of PTEN inactivation in accelerating SCLC in genetic mutant mouse models suggests that the PTEN-associated signaling pathway is a strong therapeutic pathway for SCLC, as long as predictive biomarkers can be identified [ 15 , 16 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a related report, it was pointed out that in the hyperglycemic mouse model, the high glucose environment can increase the expression of HIF-1α through glucose-responsive carbohydrate response element binding protein (ChREBP), which leads to an increase in the expression of HIF-1α [ 43 , 44 ]. In addition, it was found in hyperglycemic patients that the hypoxia-inducible factor 1α–6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (PFKFB3) pathway and activation of the PI3K/AKT pathway was induced to increase the expression of HIF-1α [ 45 , 46 ]. An animal model of pancreatic cancer with hyperglycemia showed that HIF-1α is abundantly expressed in cancer cells [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%